Being there : culture and formation in two theological schools - Carroll, Jackson W. (Religion in America series (Oxford University Press), 1997)
This text offers a view of theological education in the USA. The authors' goal is to understand the way in which institutional culture affects the outcome of the educational process. They undertake ethnographic studies of two seminaries - one evangelical and one mainline Protestant.